A Splice Variant of ASC Regulates IL-1β Release and Aggregates Differently from Intact ASC. (15th September 2009) - Matsushita, Kazuhiko; Takeoka, Michiko; Sagara, Junji; Itano, Naoki; Kurose, Yuka; Nakamura, Akihiro; Taniguchi, Shun'ichiro
Abstract : The apoptosis-associated speck-like protein containing a caspase recruit domain (ASC) is involved in apoptosis and innate immunity and is a major adaptor molecule responsible for procaspase-1 activation. ASC mRNA is encoded by three exons: exons 1 and 3 encode a pyrin domain (PYD) and caspase recruit domain (CARD), respectively, and exon 2 encodes a proline and glycine-rich (PGR) domain. Here, we identified a variant ASC protein (vASC) lacking the PGR domain that was smaller than full length ASC (fASC) derived from fully transcribed mRNA and searched for differences in biochemical and biological nature. Both fASC and vASC were found to activate procaspase-1 to a similar degree, but the efficiency of IL-1β excretion was significantly higher for vASC. There was also a marked structural difference observed in the fibrous aggregates formed by fASC and vASC. These results suggest that although the PGR domain is dispensable for procaspase-1 activation, it plays an important role in the regulation of the molecular structure and activity of ASC.